ПРАВОВАЯ ПРИРОДА ПРАВООТНОШЕНИЙ СОБСТВЕННОСТИ В РОССИЙСКОЙ ФЕДЕРАЦИИ - Мухтасарова, Татьяна Радиковна (ВЕРХОВЕНСТВО ПРАВА, 2016)
In the history of a civilization the phenomenon of a private property has exclusive value, expresses one of global tendencies of social and economic development. The property right appeared in an extreme antiquity, having arisen together with society. Historians connect allocation of a legal private property institution with the period of the Roman republic. Even later, in the period of the Middle Ages, the institute of the property right has no so broad development in Europe, as in Rome. The subsequent New time and formation of new European civilization specified typology of communities of people, the maintenance of the contractual relations, standards and norms of a hostel. The capitalist way of production placed the accents, having created social structure of society according to the property relation on means of production.
Keywords: собственность; право собственности; государство; имущество; вещь; наследство; налогообложение; экономика; владение; пользование; распоряжение.